Skull osteomyelitis as a rare complication of cat scratch disease - Yaseen Rafee (Thieme Medical and Scientific Publishers Pvt. Ltd., 2018)
Bartonella henselae, the causative agent of cat scratch disease (CSD), is one of the most common causes of regional lymphadenitis in children. Other less common manifestations of B. henselae infection including fever of unknown origin, neuroretinitis, and osteomyelitis are being increasingly recognized. We describe a 3-year-old female with a recent history of typical CSD involving lymph nodes who developed osteomyelitis of the skull, a very rarely recognized complication of this infection.